CRIMINOLOGICAL STUDY OF A THIRD PERSON'S AGENCY THAT DISTURBS ANOTHER'S MARRIAGE RELATIONSHIP - Ginting, Arief Asyari (Inspiring Law Journal, 2025)
When viewed from the criminological aspect of the cause of adultery committed by a third party that disrupts the marital relationship of another person, then the background factor that can be found is due to a strained relationship between the husband and wife in their household. This strain ultimately opens up opportunities for the presence of a third person who has the potential to damage the marital relationship of the married couple. The presence of a third person can provide new motivation and warmth from the rift in the household of the married couple, especially if the relationship continues to an intimate relationship with the party who is having an affair. The implementation and application of the law in handling the perpetrators and parties involved in the affair that causes a rift and disrupts the marital relationship of another person, then in the elements of the criminalization, the perpetrators can be charged with articles and legal sanctions as stipulated in Law Number 1 of 2023 concerning the Criminal Code, Article 284 paragraph (1) perpetrators of adultery who can be threatened with imprisonment if one of the perpetrators of the adultery is already legally married to another person. In Article 411 of the new Criminal Code concerning adultery which carries a penalty of 1 year in prison and a fine of IDR 10 million. This article is an absolute complaint offense, which means it can ensnare someone if there is a complaint from an interested party. In this case, the interested party is a husband or wife who is bound by marriage and/or their parents. However, this article cannot be a reason for just anyone to report or raid or conduct an inspection without such a complaint.